Effect of exercise therapy on PICC-associated venous thromboembolism: A meta-analysis. (March 2023) - Liu, Aiping; Liu, Xiaoqing; Li, Zhaoyang; Lai, Chunyan; Tan, Jing
Background: Peripherally inserted central catheter (PICC) is widely used in clinical practice because of its long retention time and easy maintenance. However, PICC-associated venous thromboembolism (VTE) is the most serious complication of PICC. Guidelines recommend exercise therapy to prevent PICC-associated VTE. However, inconsistent findings have been reported across the literature. This study conducted a meta-analysis to further evaluate the effect of exercise therapy on PICC-associated VTE. Methods: We searched CNKI, Wanfang database, Chinese Science and Technology Journal Full Text Database, PubMed, Embase, Web of Science and Cochrane Library databases and included all randomized controlled trials (RCTs) of exercise therapy for the prevention of PICC-associated VTE. Two investigators independently screened the literature, extracted information, and evaluated the risk of bias for eligible RCTs. Meta-analysis was conducted by RevMan5.4 software. Results: Eleven RCTs were included, including 1919 patients. Meta-analysis showed that the incidence of PICC-associated VTE was lower in the exercise therapy group than in the usual care group (RR = 0.30, 95% CI: 0.22–0.41, p < 0.00001).Exercise therapy increased the axillary vein maximum velocity (SMD = 0.93, 95% CI: 0.58–1.28, p < 0.00001) and the axillary vein time-mean flow velocity (SMD = 0.86, 95% CI: 0.53–1.20, p < 0.00001). Subgroup analysis showed statistically significant differences for the incidence of PICC-associated VTE for intervention times<4 weeks (RR = 0.26, 95% CI: 0.17–0.40, p < 0.00001) and intervention times≥4 weeks (RR = 0.35, 95% CI: 0.22–0.54, p < 0.00001). For axillary vein maximum velocity, the difference was statistically significant for both intervention time <4 weeks (SMD = 0.73, 95% CI: 0.55–0.91, p < 0.00001) and intervention time ≥4 weeks (SMD = 1.18, 95% CI: 0.18–2.19, p = 0.02). For axillary vein time-mean flow velocity, the intervention time <4 weeks (SMD = 0.75, 95% CI: 0.46–1.04, p < 0.00001), and the difference was statistically significant; while ≥4 weeks, the difference was not statistically significant (SMD = 1.14, 95% CI: −0.07 to 2.35, p = 0.06). Conclusions: Exercise therapy improved venous blood flow velocity and effectively reduced the incidence of PICC-associated VTE. However, RCTs with large samples and high quality are needed to further evaluate the effectiveness of exercise therapy in PICC patients.